The shaping of genetic variation in edge‐of‐range populations under past and future climate change. (26th July 2013) - Razgour, Orly; Juste, Javier; Ibáñez, Carlos; Kiefer, Andreas; Rebelo, Hugo; Puechmaille, Sébastien J.; Arlettaz, Raphael; Burke, Terry; Dawson, Deborah A.; Beaumont, Mark; Jones, Gareth
Abstract: With rates of climate change exceeding the rate at which many species are able to shift their range or adapt, it is important to understand how future changes are likely to affect biodiversity at all levels of organisation. Understanding past responses and extent of niche conservatism in climatic tolerance can help predict future consequences. We use an integrated approach to determine the genetic consequences of past and future climate changes on a bat species, Plecotus austriacus . Glacial refugia predicted by palaeo‐modelling match those identified from analyses of extant genetic diversity and model‐based inference of demographic history. Former refugial populations currently contain disproportionately high genetic diversity, but niche conservatism, shifts in suitable areas and barriers to migration mean that these hotspots of genetic diversity are under threat from future climate change. Evidence of population decline despite recent northward migration highlights the need to conserve leading‐edge populations for spearheading future range shifts.